A Developmental-Ecological Perspective On The Role Of Spirituality In The Development Of Meaningfulness In Adolescent Boys - Leblanc, Gess (Research in the social scientific study of religion, 2008)
As a result of recent incidents of school violence, a number of approaches have been undertaken in an effort to address the risk factors typically associated with violent behavior among adolescent boys. Among the risk factors generally identified is the need for boys to view their lives as meaningful. The purpose of this research is to examine how spirituality serves as a protective factor against aggressive and violent behavior among boys by investigating how it helps them to view their lives as being meaningful. Focusing on schools as a particularly important context for adolescent development, this work demonstrates that the use of pedagogical practices that support and foster spirituality promotes positive development and may aid in the reduction of specific risk factors associated with violent and antisocial behavior among adolescent boys.